Sosialisasi Upaya Peningkatan Minat Baca Pada Siswa-Siswi SD Negeri 020 Manggar Baru - Rinto; Latumeten, Anna Anganita Theresia; Firdaus, Wahyu Achmad (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2024)
The socialization program on reading literacy aims to increase the reading interest efforts of the students of Public Elementary School 020 Manggar Baru through socialization and book donations for the library. Low reading interest at the primary school level is often a challenge in developing children's literacy. This activity combines the socialization method with book donation as an innovative strategy. The socialization method involves interaction between teachers and students in activities designed to increase reading awareness and interest. In addition, the book donation program was conducted to enrich the school library collection, giving students wider access to varied and interesting reading materials. This socialization activity involved students from class IV B of Public Elementary School Negeri 020 Manggar Baru as research subjects. The results showed a significant increase in students' reading interest and active participation in reading activities, and an enriched library encourages reading interest by providing diverse sources of information. The result of the socialization activities is that the combination of socialization and book donation can be an effective model in increasing elementary school students' reading interest while strengthening the library's role as a learning center. This model can be adopted by other schools to support children's literacy development. Keywords: effective model, reading habits, reading interest, library,